Corona Corporation Nickel Plate Mine - S. Haggarty (Canadian Institute of Mining, Metallurgy and Petroleum, 1991)
"Wholly owned by Corona Corporation, the Nickel Plate Mine is an open pit, gold mining operation located near Hedley, 50 km west of Penticton, in Southern British Columbia.Milling capacity is 3,400 SDT /Day with an average feed grade of 0.080 Oz Au/Ton. Gold processing involves three stage grinding including tertiary pebble milling, two stage cyanide leaching and filtering and Merrill-Crowe zinc precipitation.A summary of process improvements required to increase milling capacity above the initial design tonnage of 2, 700 SDT /Day are described -Installation of a 42"" x 65"" Allis Chalmers Gyratory crusher replacing a 42"" x 48"" Traylor jaw crusher.Installation of polyurethane screen panels replacing woven wire cloths on an 8' x 20 ft triple deck screen.Installation of a hopper clarifier to reduce filtrate turbidity.Automated control of solution balancing and effluent treatment circuits.INTRODUCTIONThis paper describes mining and milling practices at the Nickel Plate Mine and details post start-up process modifications which were required to attain design tonnage.Wholly owned by Corona Corporation, the Nickel Plate Mine is an open pit, gold mining operation located near Hedley, 50 km west of Penticton, in Southern British Columbia.Mining capacity from the open pit is approximately 32,000 TPD with an average waste/ore ratio of 8.4:1.Milling capacity is 3,400 SOT/Day, above initial design tonnage of 2,700 SOT/Day. Feed grade averages 0.08 Oz Au per ton yielding 85,000 troy ounces of gold per year."